PENGEMBANGAN UMKM MANDIRI MELALUI POTENSI WISATA WADUK CITANI DI DESA WOTANSARI GRESIK - Mauliddah, Nurullaili; Julia, Dia Dewi; Mochklas, Mochamad; Rusmawati, Zeni (CV. Kalimasada Group, 2023)
Community service activities are based on discovering problems faced by the community or the environment after observations are made so that programs can be determined to suit their needs. Wotansari Village, one of the villages in Gresik Regency, has a new tourist attraction, which BUMDEs Giri Asih manages. However, many MSMEs who operate in the reservoir feel they need help managing their finances well and are still dependent on bank loans or loan sharks. In addition, the promotion of the pool still needs to be improved. Through community service activities, several programs implemented are: Educational activities on financial management towards family finances and independent businesses, Making promotional videos and photo spots as new vehicles, Optimizing village websites for independent population services. Based on the evaluation results, it is known that this community service activity has received a good response from the community, as evidenced by an increase in community understanding of good financial management, knowledge of the use of village websites for self-service, and the increasing introduction of the Waduk Citani to the general public.